Reciprocal interaction between cortical SST and PV interneurons in top–down regulation of retinothalamic refinement - Qiufen Jiang; Sherry Jingjing Wu; Gord Fishell; Chinfei Chen (Proceedings of the National Academy of Sciences, 2025)
Refinement of thalamic circuits is crucial for the proper maturation of sensory circuits. In the visual system, this process is regulated by corticothalamic feedback during the experience-dependent phase of development. Yet the cortical circuits modulating this feedback remain elusive. Here, we demonstrate opposing roles for cortical somatostatin (SST) and parvalbumin (PV) interneurons in shaping retinogeniculate connectivity during the thalamic sensitive period (P20-30). Early in the refinement process, SST interneurons promote the strengthening and pruning of retinal inputs in the thalamus, as evidenced by disrupted synaptic refinement following their ablation. In contrast, PV interneurons, which mature later, act as a brake on this refinement, with their ablation leading to enhanced pruning of retinogeniculate connections. Notably, manipulating the relative balance between these inhibitory circuits can regulate sensory deprivation-induced retinogeniculate remodeling. Taken together, our findings show that cortical SST and PV interneuron circuits drive experience-dependent reciprocal antagonism that gates cortical feedback regulation of feedforward thalamic refinement.